Nitrogen Contribution by Palm Oil Mill Effluent to Young Oil Palm (Elaeis guineensis Jacq.) as measured by 15N Isotope Dilution Technique - T., Mohd Hashim; Abdul Rahman, Zaharah (Universiti Putra Malaysia Press, 1994)
Palm oil mill effluent (POME) is an organic waste material produced at the oil palm mills. In its raw form, POME is highly polluting due to its high content of biological and chemical oxygen demand. It must be treated before being discharged into the waterways. But in view of its high nutrient content, it can be recycled to the soil as a fertilizer for agricultural crops. Two nursery trials were conducted using oil palm (Elaeis guineensis Jacq.) seedlings planted in polybags containing 8 kg Selangor series soil (Aeric Tropaquept) to evaluate the nitrogen contribution by POME applied to the soil. The trials were carried out for a period of 40 weeks using the nitrogen-15 isotope dilution technique. The nitrogen in the plants contributed by the POME at various times was calculated using the isotope dilution procedure described by Fried and Dean (1952). It was found that the amount of nitrogen contributed by POME in both the experiments ranged between 4.9 to 12.1 percent of the total nitrogen content of the POME applied. A higher N was utilized from POME that contained higher total solids.